The Influence of Self-Efficacy on the Anxiety Levels of Students at the Faculty of Medicine Muhammadiyah Purwokerto University - Harum, Resmi Syahidah (UM Purwokerto Press, 2025)
Anxiety is closely related to fear, where fear arises from something threatening. The aim of this research is to determine whether there is an influence of Self-Efficacy on the anxiety level of students at the Faculty of Medicine, Muhammadiyah University, Purwokerto. The hypothesis is that there is an influence of Self-Efficacy on the level of anxiety in Medical Students at Muhammadiyah University, Purwokerto. The higher the level of Self-Efficacy, the lower the level of anxiety students will have. This research is descriptive and analytical research. The results of this research provide answers that there is an influence of Self-Efficacy on the anxiety level of students at the Faculty of Medicine, Muhammadiyah University, Purwokerto.